Gasification operational characteristics of 20-tons-Per-Day rice husk fluidized-bed reactor. (May 2021) - Park, Sung Jin; Son, Seong Hye; Kook, Jin Woo; Ra, Ho Won; Yoon, Sang Jun; Mun, Tae-Young; Moon, Ji Hong; Yoon, Sung Min; Kim, Jae Ho; Kim, Yong Ku; Lee, Jae Goo; Lee, Do-Yong; et al.
Abstract: Converting rice husk into energy is a promising method of generating renewable energy and reducing greenhouse gas emissions. The characteristics of rice husk gasification were investigated at an equivalence ratio (ER) of 0.20–0.35 and a gasifier temperature of 700–850 °C in a 20-tons-per-day (TPD) bubbling fluidized-bed gasifier system. The optimal conditions of the gasification operation were an ER of 0.20 and gasifier temperature of 800 °C. The low heating value of the gas product and cold gas efficiency were 1373.18 kcal/Nm 3 and 70.75%, respectively. After passing the generated gas through the gas cleaning units, it was confirmed that the tar in the product gas was removed with an efficiency of 98%. The cleaned product gas was used for the operation of 400 kWe gas engine. Pressure loss often occurred at the bottom of the gasifier during the gasification operation; we found that the agglomerates generated by the gasification process caused it. Computational particle fluid dynamics simulations were performed to investigate the fluidizing characteristics of agglomerates. To prevent the pressure loss caused by the agglomerates, the stable control of temperature inside the gasifier is needed and an ash removal device remove agglomerates should be installed to maintain stable long-term operation. Highlights: Operation of a rice husk bubbling fluidized bed gasifier was investigated. The optimum equivalence ratio was found to be 0.20 The tar removal efficiency of the gas cleaning devices was 98%. Fluidizing characteristics of agglomerates were analyzed by experiments and CPFD.